2016
DOI: 10.1038/ncomms12630
|View full text |Cite
|
Sign up to set email alerts
|

ATRA mechanically reprograms pancreatic stellate cells to suppress matrix remodelling and inhibit cancer cell invasion

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive malignancy with a dismal survival rate. Persistent activation of pancreatic stellate cells (PSCs) can perturb the biomechanical homoeostasis of the tumour microenvironment to favour cancer cell invasion. Here we report that ATRA, an active metabolite of vitamin A, restores mechanical quiescence in PSCs via a mechanism involving a retinoic acid receptor beta (RAR-β)-dependent downregulation of actomyosin (MLC-2) contractility. We show that ATRA redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
183
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(190 citation statements)
references
References 68 publications
5
183
0
2
Order By: Relevance
“…Using clinical specimen and experimental mouse models, Laklai et al identified a distinct, highly stiff, matricellular-stromal phenotype that was specifically associated with reduced epithelial transforming growth factor (TGF)-β signalling, elevated β-integrin mechano-signalling and Stat3 activation resulting in therapeutic resistance and significantly shortened survival in mice and humans 37. In line with these findings, ATRA, an active metabolite of vitamin A, was reported to reprogram mechanical quiescence in PSCs via a mechanism involving a retinoic acid receptor beta-dependent downregulation of actomyosin contractility 38. Furthermore, Rho kinase (ROCK) signalling, Yes-associated protein 1 and Janus kinase 2 and signal transducer and activator of transcription 3 signalling pathways have been associated with tissue tension and tumour cell contractility 39–41…”
Section: Introductionmentioning
confidence: 83%
“…Using clinical specimen and experimental mouse models, Laklai et al identified a distinct, highly stiff, matricellular-stromal phenotype that was specifically associated with reduced epithelial transforming growth factor (TGF)-β signalling, elevated β-integrin mechano-signalling and Stat3 activation resulting in therapeutic resistance and significantly shortened survival in mice and humans 37. In line with these findings, ATRA, an active metabolite of vitamin A, was reported to reprogram mechanical quiescence in PSCs via a mechanism involving a retinoic acid receptor beta-dependent downregulation of actomyosin contractility 38. Furthermore, Rho kinase (ROCK) signalling, Yes-associated protein 1 and Janus kinase 2 and signal transducer and activator of transcription 3 signalling pathways have been associated with tissue tension and tumour cell contractility 39–41…”
Section: Introductionmentioning
confidence: 83%
“…Agents targeting LOX activity could decrease collagen crosslinking, thereby reducing the density of the tumour stroma and increase the effectiveness of anticancer therapies 279282 . The vitamin D receptor ligand calcipotriol 283 and all-trans retinoic acid (ATRA) 284 are other agents that reduced fibrosis in experiments with PDAC models.…”
Section: Tumour-stroma Targeting Strategiesmentioning
confidence: 99%
“…Similarly, all trans-retinoic acid (ATRA), the physiological active metabolite of vitamin A, restores mechanical quiescence in PSCs via activation of the retinoic acid receptor beta (RAR-β) and down regulation of actomyosin contractility, which suppresses the ability of PSCs to apply forces and mechanosense matrix rigidity. Mechanically quiescent PSCs are unable to remodel and stiffen the matrix, and this creates a microenvironment that is not favourable for pancreatic cancer cell invasion (figure 2) [35]. Notably, PSCs were removed from remodelled collagen/matrigel matrices before cancer cell invasion in these in vitro experiments; thus, the reduced ability of cancer cells to invade was related to the mechanical and/or topological changes in the ECM.…”
Section: Reprogramming Cell Mechanics Induces Quiescence In Pscs Supmentioning
confidence: 99%
“…Bottom, bright field images of PSC and its corresponding force map. Panel reproduced from [35]. CC BY 4.0.…”
Section: Atomic Force Microscopymentioning
confidence: 99%